Anticoagulation clinic drive-up service during COVID-19 pandemic in Qatar - Eman Alhmoud (13955766) (2022)
Coronavirus Disease 2019 (COVID-19) is a pandemic affecting many countries worldwide. Given the increasing incidence especially in elderly and individuals with comorbid conditions, it is advised by health authorities to stay home if possible, maintain social distancing and stay away from those who are sick or could be infected. Patients with comorbidities especially cardiovascular disease are at higher risk of getting infected with COVID-19 and have worse prognosis. Among efforts to safely manage warfarin patients during this pandemic, we introduced a hospital drive-up anticoagulation testing service. This service can reduce the risk of exposure of anticoagulation patients to COVID-19 by reducing the contact time with the different personnel at the hospital and by maintaining those patients at a safe distance from others Other Information Published in: Journal of Thrombosis and Thrombolysis License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11239-020-02206-4